Anatomy of Acacia mangium grown in Malaysia - Sahri, Mohd. Hamami; Ibrahim, Faridah Hanum; Ab Shukor, Nor Aini (Brill, 1993)
A study on the tissue proportions and fibre dimensions of plantation-grown Acacia man gium was carried out, Ten selected trees from two age groups (4- and 8-year-old) were obtained from plantation forests in Selangor. Disks were taken from four sampling heights . Acacia mangiurn wood is diffuse-porous with mostly solitary vessels . The rays are uniseri ate. The average percentage of fibres, vessels and rays of 4-year-old and 8-year-old sam ples are 85.8%, 9.1%, 5.2% and 84.8% , 9 .8%,5.3%, respectively. Acacia is a short fibred tropical species. The average fibre length, fibre diameter, fibre lumen diameter and fibre wall thickness are 934, 24, 17 and 3.3 11m for 4-year-old samples and 1017,20, 12 and 4.3 urn for S-year-old samples, re spectively. The samples near the pith have the shortest fibres and the length increases toward the bark. Fibre length also tends to decrease with height. The vessel percentage decreases with increasing height.